Wandering workers : mores, behavior, way of life, and political status of domestic Russian labor migrants - Pli͡usnin, I͡U. M. (I͡Uriĭ Mikhaĭlovich); Zausaeva, I͡A. D.; Zhidkevich, N. N.; Pozanenko, A. A. (Soviet and post-Soviet politics and society ;, 2015)
"This timely book offers a fresh perspective on the issue of contemporary migratory labor, otkhodnichestvo, in Russia -- the temporary departure of inhabitants from small towns and villages for short-term jobs in the major cities of Russia. Although otkhodnichestvo is a mass phenomenon, it is not reflected in official economic statistics. Based on numerous interviews with otkhodniks and local experts, this stunningly original work focuses on the central and northern regions of European Russia. The authors draw a social portrait of the contemporary otkhodnik and offer a sociological assessment of the economic and political status these 'wandering workers' live with"--Provided by publisher